Frankenstein - Mary Shelley (Open Library, 1818)
The world’s most famous work of horror fiction: a devastating exploration of the limits of human creativity. Nominated as one of America’s best-loved novels by PBS’s The Great American Read Mary Shelley's timeless gothic novel presents the epic battle between man and monster at its greatest literary pitch. In trying to create life, the young student Victor Frankenstein unleashes forces beyond his control, setting into motion a long and tragic chain of events that brings Victor to the very brink of madness. How he tries to destroy his creation, as it destroys everything Victor loves, is a powerful story of love, friendship, scientific hubris, and horror. Based on the third edition of 1831, this Penguin Classics edition, with an introduction and notes by Maurice Hindle, contains all the revisions Mary Shelley made to her story, as well as her 1831 introduction and Percy Bysshe Shelley’s preface to the first edition. It also includes as appendices a select collation of the texts of 1818 and 1831 together with "A Fragment" by Lord Byron and Dr John Polidori’s "The Vampyre: A Tale." For more than seventy years, Penguin has been the leading publisher of classic literature in the English-speaking world. With more than 1,700 titles, Penguin Classics represents a global bookshelf of the best works throughout history and across genres and disciplines. Readers trust the series to provide authoritative texts enhanced by introductions and notes by distinguished scholars and contemporary authors, as well as up-to-date translations by award-winning translators.
Métadonnées bibliographiques et couvertures référencées via Open Library / Internet Archive. Vérifier les droits de couverture selon usage final.
Keywords: science; créature; Shelley; classique